Association of triglyceride to HDL cholesterol ratio with cardiometabolic outcomes. (March 2019) - Yang, May; Rigdon, Joseph; Tsai, Sandra A
Electronic medical records (EMRs) offer a potential opportunity to identify patients at high risk for cardiometabolic disease, which encompasses type 2 diabetes and cardiovascular disease (CVD). The objective of this retrospective cohort study is to use information gathered from EMR to investigate the association between triglyceride to high-density lipoprotein cholesterol ratio (TG/HDL-C) and cardiometabolic outcomes in a general population of subjects over 50 years of age during a follow-up period of 8–9 years. TG/HDL-C was recorded for each of 1428 subjects in 2008, and diagnoses of type 2 diabetes and CVD were recorded through chart review until 2017. Cox proportional hazards models controlling for demographic characteristics and other risk factors demonstrated that high TG/HDL-C (>2.5 in women or >3.5 in men) was significantly associated with increased incidence of type 2 diabetes (HR 1.66; 95% CI 1.07 to 2.57; p=0.0230). There was also a suggested association between high TG/HDL-C and incidence of CVD (HR 1.51; 95% CI 0.98 to 2.35; p=0.0628). These findings suggest that using TG/HDL-C, which can be easily calculated from data in an EMR, should be another tool used in identifying patients at high cardiometabolic risk.